Strangers : a memoir of marriage [compact disc, unabridged] - Burden, Belle (Penguin Random House, 2026)
In March 2020, Belle Burden was safe and secure with her family at their house on Martha's Vineyard, navigating the early days of the pandemic together. Then, with no warning or explanation, her husband of twenty years announced that he was leaving her. Overnight, her caring, steady partner became a man she hardly recognized. He exited his life with her like an actor shrugging off a costume. In this memoir, Burden revisits her marriage, searching for clues that her husband was not who she always thought he was.